1997
DOI: 10.1136/pgmj.73.862.519
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurantoin rechallenge and recurrent toxicity

Abstract: There are a limited number of pathological responses to noxious stimuli, including drugs, and drug-induced (iatrogenic) disease may be difficult to distinguish from other causes. We describe the case of a woman who had two different serious reactions in association with two courses of the antibiotic nitrofurantoin given 16 On specific questioning about whether she might be taking any medications, particularly for prevention of cystitis, she recalled that she had been prescribed by her general practitioner a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several studies have reported known serious adverse events after short‐term or prolonged use of nitrofurantoin with or without renal impairment leading to neuropathy, pulmonary disorders, and blood dyscrasias 1–6 . The neuropathy occurs more frequently in women and in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported known serious adverse events after short‐term or prolonged use of nitrofurantoin with or without renal impairment leading to neuropathy, pulmonary disorders, and blood dyscrasias 1–6 . The neuropathy occurs more frequently in women and in the elderly.…”
Section: Discussionmentioning
confidence: 99%